Panel of serum protein biomarkers to grade the severity of traumatic brain injury - Anada, Raj Poovindran; Wong, Kum Thong; Jayapalan, Jaime Jacqueline; Hashim, Onn Haji; Ganesan, Dharmendra (Wiley-VCH Verlag, 2018)
The Glasgow Coma Scale (GCS), which classifies patients into mild, moderate or severe traumatic brain injury (TBI), is a system used to prioritize treatment and prognosticate the severity of head injury. In this study, sera of patients with various stages of TBI, as well as control subjects, were analyzed to screen for proteins that may be used to complement the GCS system. By subjecting pooled serum samples to iTRAQ analysis for quantitative comparison of protein abundance, and attesting their altered levels using ELISA, we have detected increased levels of serum amyloid A, C-reactive protein, leucine-rich alpha-2-glycoprotein, lipopolysaccharide-binding protein, fibronectin, vitronectin and alpha-1-antichymotrypsin in patients across all strata of TBI relative to the controls. However, kininogen was decreased only in moderate and severe TBI, whereas apolipoprotein E and zinc-alpha-2-glycoprotein were only increased in severe TBI. Hence, we propose a panel of serum biomarkers, which if analyzed within 24 h of the injury, can be used to diagnose patients with TBI into mild, moderate or severe stratification objectively, thus complementing the traditional GCS.